Estudo anatômico e distribuição das papilas valadas no gato doméstico - Guimarães, Gregório Corrêa [UNESP]; Machado, Márcia Rita Fernandes [UNESP]; Santos, André Luiz Quagliatto; Miglino, Maria Angélica (My University, 2007)
The tongue of domestic animals varies in size and shape and according to these animals feeding habits, there are different degrees of tongue surface specialization. At the dorsal surface of the tongue lingual papillae can be observed, such as the vallate papillae, related to taste perception. With the help of a magnifying glass, differences in the number, size and distribution of vallate papillae were studied. Fifty five tongues of adult domestic cats from both sexes (38 females and 17 males) were analyzed. The samples were fixed in 10% buffered formalin. The vallate papillae were found to be symmetrically distributed on 21 tongues (38.18%). However, it was observed that in some of the tongues the number of vallate papillae varied when one side of the tongue was compared to its contralateral side. The vallate papillae showed different shapes: elongated (42.58%), oval (31.61%), round (25.48%) and pear shaped (0.33%). The vallate papillae were classified into 10 different categories: symmetrical I (2 right and 2 left), II (3:3), III (4:4) and asymmetrical IV (3:2), V (4:2), VI (2:3), VII (4:3), VIII (5:3), IX (3:4) and X (4:5). Measurements of length and width were made with averages of 0.84 ± 0.23 mm and 0.55 ± 0.18 mm, respectively, besides the calculation of the total area of these papillae per tongue, that showed average of 2,74 ± 0,31 mm 2 in males and 1,94 ± 0,14 mm 2 in females However, upon examining the lingual papillae of the cat tongues, specimens demonstrating 7, 8 or 9 vallate papillae, arranged in pairs (4:3, 5:3, 3:4 and 4:5) by category, were observed in this study but not cited in the literature.
Anatomic study and distribution of the vallate papillae in domestic cats
Keywords: Gustatory papillae; Tongue; Vallate papillae; Animalia; Felis catus; Pyrus